INFORMATION SYSTEM DESIGN OF SHAHIRAH RAHMAWATI DENTIST'S PRACTICE BASED ON WEB AND SMS GATEWAY USING THE RATIONAL UNIFIED PROCESS METHODOLOGY - M.Hasim Siregar (Universitas Islam Kuantan Singingi, 2021)
Dental practices is one of the services in the field of Health has already managed independently, so it is required to provide the best service to the society with good management. In good management, it does not need to be done repeatedly, for example, nurses or employees check, store, or search for medical records manually even though only on the same variable. In the dental practice of Shahirah Rahmawati, appointments are still made by telephone and recorded on paper so it is less effective and less practical. The recording of dental medical records and medicines are also done manually. So that why the research doing to design an information system using an object-oriented approach. On the whole process, from input data, and presentation of reports aims to make easy for users and to schedule regular patient visits using SMS Gateway.